Estacionalidad de las especies de aves residentes y migratorias altoandinas en el lado peruano de la cuenca del Titicaca - Pulido Capurro, Víctor (2018)
The birds that habit in the basin of Titicaca lake have a wide distribution which includes, mountain ranges and "pajonales of puna". The Titicaca lake is recognized by the Ramsar Convention as Wetland of International Importance. In the present work, 135 species comprised in 17 orders, 33 families and 83 genders have been registered. With regard to seasonality, 95 species are residents and 40 are from other latitudes, of which 17 species are Nearctic migrants, 10 migratory species come from the Austral Region, and 13 species make vertical migrations from The Peruvian Andes to the coastal region. For the time they spend in most environments, 81 species are terrestrial, 45 aquatic and 9 in flight. Therefore, the results obtained have determined that the species of resident birds spend all year in the Titicaca basin: the neartic migrants from September to March, the austral migratory birds between April and August and those that make altitudinal migrations to the coastal region, from May to August.